Assessment of quality of life and erectile dysfunction in a sample of diabetic Egyptian men. Issue 2 (June 2016) - Morsy, Hanan; Essam, Mohammed; Soliman, Mona; Badry, Fatma
Abstract : Objective: Diabetes mellitus may cause sexual dysfunction among men, medical complications, and psychological disturbances. This study was carried out to assess quality of life and erectile dysfunction among a sample of diabetic men. Materials: In the current study, we included 500 diabetic men attending the Andrology outpatient clinic, Diabetes outpatient clinic, diabetic foot outpatient clinic, Assiut University Hospitals, Egypt. The participants were evaluated using the Arabic version of the International Index of Erectile Function questionnaire and the Arabic version of SF-36 questionnaire. Results: The mean age was 53.13 ± 11.92 years. Of the 500 participants, erectile dysfunction was severe in 112 patients (22.4%), moderate in 82 patients (16.4%), mild-to-moderate in 116 patients (23.2%), mild in 158 patients (31.6%), and 32 patients (6.4%) had no impairment. Erectile dysfunction increased with age of participants, smoking, and duration of diabetes. Conclusion: Lifestyle changes and clinical management of accompanying medical complications with better understanding of the psychological problems that face diabetic people with erectile dysfunction can lead to better management and reduction of the incidence of erectile dysfunction.